Issues related to the protection and use of fruit tree and grapevine genetic resources in Albania - Sotiri P.; Cakalli D. (Italo-Albanian cooperation for the enhancement of plant biodiversity, 2001)
Urgent issues are certainly their in-situ tracing, inventory and protection and the ex situ study, evaluation and economic use of the majority of them for the purpose of the sustainable development of agriculture in general, and viticulture in particular, both in hilly and mountainous zones of Albania. Finally, the formulation of an effective legislation in the framework of the global strategy for biodiversity ad the establishment of the Genetic Bank for plant-farming, as a separate scientific unit (given the importance and the concrete situation of our country), would constitute the concrete measures for the protection, evaluation and use of biodiversity in Albania.
2. Seminar: Italo-Albanian cooperation for the enhancement of plant biodiversity, 2000/10/26-28, Tirana (Albania)